Verbal And Non-Verbal Characteristics Of Approval Speech Act - Bigunova, Natalia; Kolegaeva, Irina (Տիգրան Մեծ)
The paper focuses on verbal and non-verbal characteristics of the approval speech act in English literary discourse. Approval evaluation object has been identified including things, ideas, facts, traditions, weather conditions, events, pieces of news and other phenomena that become evaluated. It has been proved in the article that approval evaluation objects never refer to the addressee‟s sphere of interests and that the approval recipient and the evaluation object of approval never overlap. The article also dwells on illocutionary aims pursued by approval speech act addressers and the perlocutionary effect of approval speech act. The central part of the paper considers lexical, morphological, syntactic, and stylistic means applied by the personages of fictional literary discourse to express approval of a particular object. Finally, non-verbal means manifesting approval have been identified. It has been found out that in fictional literary discourse, the emotional state of the approval addresser is specified by the verbalised kinemes. The latter also signal whether the approving utterance is sincere or not.
Keywords: Language and Literature; Speech art